2012
DOI: 10.1111/j.1745-4549.2012.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Hot Air and Infrared Drying of Parboiled Rice: Kinetics and Qualities Aspects

Abstract: The objectives of this study were to analyze the effects of drying employing three different heat sources on drying kinetics and to evaluate qualities of parboiled rice after drying. Drying temperature was varied between 60 and 100C. Power of infrared (IR) heat source was fixed at 1,000 and 1,500 W and air flow rate was fixed at 1.0 ± 0.2 m/s. The three drying strategies composed of hot air (HA), IR and combined HA + IR drying. The experimental results were simulated using various equilibrium moisture content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 46 publications
7
35
0
1
Order By: Relevance
“…No variation in cooking time as a function of the drying temperature was observed (Figure 6a). Bualuang et al () reported that the cooking time and water absorption of the parboiled rice dried by IR at temperatures between 60 and 100°C did not change, mainly because it was the same gelatinization temperature between the parboiled rice samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No variation in cooking time as a function of the drying temperature was observed (Figure 6a). Bualuang et al () reported that the cooking time and water absorption of the parboiled rice dried by IR at temperatures between 60 and 100°C did not change, mainly because it was the same gelatinization temperature between the parboiled rice samples.…”
Section: Resultsmentioning
confidence: 99%
“…Bualuang et al () studied the drying of parboiled rice with IR (1,000 to 1,500 W) and hot air with a temperature range of 60 to 100°C. These authors reported an increase in the hardness of the rice grains according to the increase of the drying temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), parboiled rice (Bualuang et al . ), paddy (Das et al . ; Laohavanich and Wongpichet ), pomegranate arils (Alaei and Chayjan ), vegetables (Hebber et al .…”
Section: Ir Radiation Heating In Different Dryersmentioning
confidence: 99%
“…As a result, the combination of IR radiation and other dying methods can be found more efficient and useful to get improved results. Various researchers have carried out IR drying and combined IR-convective drying for food and agriculture products such as onion (Lewicki et al 1998;Wang 2002;Sharma et al 2005), potato Abe 1998, 1999;Tan et al 2001), pineapple (Tan et al 2001), carrot (Togrul 2006;Mihoubi et al 2009;Wu et al 2014;Doymaz 2015), banana (Nimmol et al 2007;Leonard et al 2008;Swasdisevi et al 2009), apple (Nowak and Lewicki 2005; Witrowa-Rajchert and Rzaca 2009), meat products (Sheridan and Shilton 1999), cashew (Hebber and Rastogi 2001), welsh onion (Mongpraneet et al 2002), industrial tomato products (Celma et al 2009a), seedless grapes (Celma et al 2009b), wet olive husk (Celma et al 2008), citrus press cake (Senevirathne et al 2010), barley Markowski et al 2007), parboiled rice (Bualuang et al 2013), paddy (Das et al 2009;Laohavanich and Wongpichet 2009), pomegranate arils (Alaei and Chayjan 2015), vegetables (Hebber et al 2004), cabbage seeds (Zhu et al 1999), potato chips (Supmoon and Noomhorm 2013) and Murta berries (Puente-Díaz et al 2013).…”
Section: Ir Radiation Heating In Different Dryersmentioning
confidence: 99%